2003
DOI: 10.1038/nm934
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a tumoral immune resistance mechanism based on tryptophan degradation by indoleamine 2,3-dioxygenase

Abstract: T lymphocytes undergo proliferation arrest when exposed to tryptophan shortage, which can be provoked by indoleamine 2,3-dioxygenase (IDO), an enzyme that is expressed in placenta and catalyzes tryptophan degradation. Here we show that most human tumors constitutively express IDO. We also observed that expression of IDO by immunogenic mouse tumor cells prevents their rejection by preimmunized mice. This effect is accompanied by a lack of accumulation of specific T cells at the tumor site and can be partly reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
1,796
6
31

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,061 publications
(1,875 citation statements)
references
References 35 publications
42
1,796
6
31
Order By: Relevance
“…10 Since its first characterization as a competitive inhibitor of IDO, 37 1-MT has become the compound of reference for IDO-blocking studies. 21,22,[38][39][40] Its ability to block IDO activation in response to LPS is demonstrated in the present study by the decreased kynurenine/ tryptophan ratio that is observed in both the periphery and the brain of 1-MT-treated mice. Since the main consequence of IDO activation is development of immunotolerance because of an inability of tryptophan-deprived T cells to proliferate and induce cytotoxicity, blockade of IDO has mainly been studied in the context of reproductive physiology and tumor immune surveillance.…”
Section: Discussionsupporting
confidence: 58%
“…10 Since its first characterization as a competitive inhibitor of IDO, 37 1-MT has become the compound of reference for IDO-blocking studies. 21,22,[38][39][40] Its ability to block IDO activation in response to LPS is demonstrated in the present study by the decreased kynurenine/ tryptophan ratio that is observed in both the periphery and the brain of 1-MT-treated mice. Since the main consequence of IDO activation is development of immunotolerance because of an inability of tryptophan-deprived T cells to proliferate and induce cytotoxicity, blockade of IDO has mainly been studied in the context of reproductive physiology and tumor immune surveillance.…”
Section: Discussionsupporting
confidence: 58%
“…To explore if a relationship exists between the expression of TDO2 and the two TrpRS, we selected glioma, breast cancer, and ovarian carcinoma as cancer entities, which are known to express high TDO2 levels 15-17 . Indeed TDO2 expression correlated with WARS but not WARS2 (Figure 2A and B), although the correlations were less strong than for IDO1 (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the question arises whether the accumulation of Trp metabolites or the depletion of Trp induces WARS. To this end we cultured A172 glioblastoma cells, which exhibit constitutive TDO2 activity 16,17 , for 5 days in complete medium without or with additional Trp supplementation. Trp supplementation, a condition that promotes the accumulation of Trp metabolites, reduced WARS expression (Figure 3A), while not affecting WARS2 (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…T cell suppression by systemic CpG-ODN treatment is mediated by IDO activity For investigation of the functional relevance of IDO expression, the tryptophan analogue 1-methyl-tryptophan (1-MT), a well-established competitive inhibitor of IDO [19,20,22], was used. OVA-induced proliferation of CFSE-labeled OT-I cells was blocked by the presence of CpG-ODN in in vitro culture (Fig.…”
Section: Cpg-odn Treatment Impairs Antigen-specific Clonal T Cell Expmentioning
confidence: 99%